Lecturer Perspective on Informal Learning Activities - Nor Atikah Md. Jizat; Muhammad Suhaimi Sulong (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to understand the influence of formal and informal learning in class. This study also intends to find an informal learning method that applied to a higher education institute. The method that applied in this study is to obtain insight into various learning processes through semi-structured interviews with several practitioners such as lecturer. After the interview is over, these interviews are transcribed and analysed with the theory-based template which has been drafted before but with an open mind emerging theme. Results show that the frequency of informal learning activities mentioned the most is searching through electronic media and the internet followed by sharing material and resources and collaborating in such discussion. This suggests that lecturers observe students formal and informal activities that students performed consciously and unconsciously. This study gives impacts and is aware of the importance to support and evoke informal learning activities within and after formal learning. The application of Informal Learning can enhance positive work ethics, communication skills, teamwork, and decision making. In addition, the informal learning model contribution is that it could establish mentorship and social events and also improve workplace relationship.